2021
DOI: 10.11622/smedj.2021129
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of post-anaesthesia care unit delirium in patients undergoing non-cardiac surgery in Singapore

Abstract: Introduction: Post-anaesthesia care unit (PACU) delirium affects 5%–45% of patients after surgery and is associated with postoperative delirium and increased mortality. Up to 40% of PACU delirium is preventable but it remains under-recognised due to a lack of awareness for its diagnosis. Nursing Delirium Screening Scale (Nu-DESC) has been validated in diagnosing PACU delirium but is not routine locally. This study aim was to use the Nu-DESC to establish the incidence and risk factors of PACU delirium in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In line with this new focus, several guidelines have been promulgated to address this issue, including the Brain Health Initiative 9 and the Safe Brain Initiative. 10 Previous pilot study in our local population has found that the incidence of PACU delirium is up to 6.2% in the elderly population, 11 while other studies found up to 25% prevalence of PACU delirium. 12 Despite the high prevalence rate, our lack of understanding of the risk factors that predispose patients to PACU delirium makes it difficult for the formulation of an evidence-based guideline for prevention of delirium.…”
Section: Discussionmentioning
confidence: 86%
“…In line with this new focus, several guidelines have been promulgated to address this issue, including the Brain Health Initiative 9 and the Safe Brain Initiative. 10 Previous pilot study in our local population has found that the incidence of PACU delirium is up to 6.2% in the elderly population, 11 while other studies found up to 25% prevalence of PACU delirium. 12 Despite the high prevalence rate, our lack of understanding of the risk factors that predispose patients to PACU delirium makes it difficult for the formulation of an evidence-based guideline for prevention of delirium.…”
Section: Discussionmentioning
confidence: 86%